Aligning the Measurement of Microbial Diversity with Macroecological Theory - Stegen, James C.; Hurlbert, Allen H.; Bond-Lamberty, Ben; Chen, Xingyuan; Anderson, Carolyn G.; Chu, Rosalie K.; Dini-Andreote, Francisco; Fansler, Sarah J.; Hess, Nancy J.; Tfaily, Malak (Frontiers in Microbiology, 2016)
The number of microbial operational taxonomic units (OTUs) within a community is akin to species richness within plant/animal (‘macrobial’) systems. A large literature documents OTU richness patterns, drawing comparisons to macrobial theory. There is, however, an unrecognized fundamental disconnect between OTU richness and macrobial theory: OTU richness is commonly estimated on a per-individual basis, while macrobial richness is estimated per-area. Furthermore, the range or extent of sampled environmental conditions can strongly influence a study’s outcomes and conclusions, but this is not commonly addressed when studying OTU richness. Here we (i) propose a new sampling approach that estimates OTU richness per-mass of soil, which results in strong support for species energy theory, (ii) use data reduction to show how support for niche conservatism emerges when sampling across a restricted range of environmental conditions, and (iii) show how additional insights into drivers of OTU richness can be generated by combining different sampling methods while simultaneously considering patterns that emerge by restricting the range of environmental conditions. We propose that a more rigorous connection between microbial ecology and macrobial theory can be facilitated by exploring how changes in OTU richness units and environmental extent influence outcomes of data analysis. While fundamental differences between microbial and macrobial systems persist (e.g., species concepts), we suggest that closer attention to units and scale provide tangible and immediate improvements to our understanding of the processes governing OTU richness and how those processes relate to drivers of macrobial species richness.